The Role of the International Labour Organization in Improving Botswana's Labour Dispute Resolution Framework: An Analysis of Key International Labour Standards - Koorapetse, Michael Sean; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2025)
The objective of this study was to examine the role of the International Labour Organization (ILO) in strengthening Botswana’s Labour Dispute Resolution Framework. Specifically, the study sought to analyse how the ILO can contribute to enhancing the effectiveness of Botswana’s system and to identify the key ILO instruments that are most relevant to labour dispute prevention and resolution. To establish a solid foundation for this inquiry and refine the research problem, a literature review was conducted to assess existing studies in this field.The research adopted a qualitative methodology, guided by an exploratory research design and anchored within an interpretivist phenomenological research strategy. A purposive sampling technique was employed to select fifteen (15) participants drawn from both Botswana and the wider SADC region. Primary data was collected through virtual semi-structured interviews, conducted mainly via electronic platforms to accommodate participants’ diverse geographic locations and ensure broad regional engagement.The findings of the study underscore the importance of the ILO as a critical partner in supporting member states to reform and strengthen their labour dispute resolution systems. The results further indicate that aligning Botswana’s framework with international labour standards would reinforce fundamental principles such as independence, due process, and equitable access to justice for both employers and employees.